Patient satisfaction with dermatology teleconsultation by using MedX. (December 2018) - Wang, Yao-Chin; Ganzorig, Bilegjin; Wu, Chieh-Chen; Iqbal, Usman; Khan, Hafash-Arshed-Ali; Hsieh, Wan-Shan; Jian, Wen-Shan; Li, Yu-Chuan (Jack)
Highlights: Patient satisfaction with the teleconsultation system used for dermatological care. Consultants and patients used Android-based MedX mobile application for telecare. High satisfaction was found to teleconsultation service in the cosmetic dermatology department. Abstract: Background: The development of telecommunication has strongly affected comprehensive scientific disciplines, including medical sciences. Objective: This study aims to assess the patient satisfaction of the teleconsultation system used for the consultation of dermatological follow-up care. Methods: The study was performed cross sectional patient satisfaction survey method conducted between February and April 2017 to determine patient satisfaction using MedX teleconsultation system. The patient sample of the current study was recruited from cosmetic laser clinic, Wanfang and Taipei Medical University hospital. The study was performed on 32 patient ( n = 32) participants. All of them were at least university graduate. Consultants and patients were handled using the Android-based MedX mobile application, which is available through an application for Google Android cellular telephones. Its application consists of a demographic information, structured step-by-step questionnaire, essential medical information about each patient, and digital images of skin lesions. Results: 28 patients completed the questionnaire. The mean ± SD age of the patients was 27.25 ± 4.039 years; 78.6% were women. The study shows that respondents have reported a high level (85.8%) of mean overall satisfaction for the teleconsultation service. The usability of the system has highest satisfaction rate of 90.5% among the other subscales especially in terms of data transfer and data displayed. Responses of the patient satisfaction questionnaire were analyzed by age and gender, no statistically significant difference between the variables was found. Conclusion: Patients have shown high satisfaction with teleconsultation service and it is well accepted in the management of cosmetic dermatology service. In the future, MedX application can be integrated into other instant messaging applications such as Line, thus allowing doctors and patients to easily communicate with each other.